MEMPREDIKSI KONDISI FINANCIAL DISTRESS BERDASARKAN RASIO LIKUIDITAS DAN RASIO PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sari , Anita Wulan; Anas, M. (Universitas Nusantara PGRI Kediri, 2017)
This study aims to test the effect of liquidity as measured by current ratio while the profitability measured by return on assets, and net profit margin in predicting financial distress at manufacturing companies listed on the Indonesia Stock Exchange. This research is made because there is still difference of research result between research one with other research. This research belongs to qualitative research. The population in this study are all manufacturing companies listed on the BEI in 2013 until 2014. While the sample of this study is determined by purposive sampling method to obtain 80 sample companies. The type of data used is secondary data obtained from www.idx.co.id. The method of analysis used is logistic regression analysis. Based on the analisys of logistik regretion within the level of 5%, therefore this research conclude that first, current ratio infuences in the prediction of financial distress in manufacture companies that have been registered in Bursa Efec Indonesia with wald test score 0.000 and significant score 0.413 > 0.05; second, return on assets has a negative influence and significance in financial distress prediction in manufacture companies that have been registered in Bursa Efec Indonesia with wald test score 1.053 and significance score 0.000 < 0.05; third, net profit margin has negative influence and significance in in financial distress prediction in manufacture companies that have been registered in Bursa Efec Indonesia with wald test score -0.200 and significance score 0.000 < 0.005.